Chinese Pinyin Text-To-Speech System (CPTTS): effects of online text-to-speech system for supporting Chinese learning among non-native speakers of Chinese as a foreign language / Goh Ying Soon, Saiful Nizam Warris and Yee Leong Yeng - Ying Soon, Goh; Warris, Saiful Nizam; Leong Yeng, Yee (2014)
Non-native learners of Chinese often experience difficulties to articulate words with precision. They need to have more practices to assist them to further improve their pronunciations. After completing the Chinese courses in the classroom, they are still lacking the ability to articulate each word with precision. Therefore, an online text-to-speech system can be handy and useful to them. This web-based Chinese pinyin text-to-speech system is specially designed and developed to facilitate the Chinese pronunciation self-learning on the web for non-native s learners. In addition, it can be a useful tool to the students of UiTM, comprising mainly of Malay native speakers and are currently using pinyin in learning Chinese. The Chinese Pinyin Text-to-Speech System (CPTTS) is used to improve the teaching of Chinese as a foreign language and further enhance students' speech on self-learning basis. Moreover, it is easy, practical, and attainable. In a nutshell, it is a helpful learning aid as the Chinese courses in UiTM are shifting towards a blended learning mode. This system will not only benefit UiTM students in particular but it demonstrates an efficient tool to all self- learners in general too. A survey was carried out to comprehend students' perceptions of the use of CPTTS to support their learning of Chinese as a foreign language. As a whole, a positive result was attained.